Perumusan Strategi Pengembangan Pariwisata Desa Nelayan Sungsang IV Kabupaten Banyusasin - Tiara Marcelia; A. Jalaluddin Sayuti; Jusmawi Bustan (Politeknik Negeri Sriwijaya, 2021)
This study aims to find out and axplain how the strategies in developing alternative tourism throught the 3A elements is Attractions, Accessiility andÂ Amenities on the Sungsang Village tourist, Banyasin District, Sumatera Selatan . The studi was located at Sungsang Village tourist, Banyasin District, Sumatera Selatan. This type of research is quantitative research with sample ofÂ 30Â visitors who had visited Sungsang Village tourist. The sampling technique used in this study was non purposive sampilng. This study use descriptive analysis, as well as using a SWOT analysis that is formulated throught the IFAS Matrix, EFAS Matrix, Grand Strategy Matrix and SWOT Matrix. The result showed that is position of Sungsang Village is in quadran I, so taht strategies taht can be used are support the agressive policies (growth oriented strategy) by the utilizing strenght to win opportunities that exist.